Effect of extraction solvents on quality of vietnamese tea (Camellia sinensis O.Kuntze) seed oil - Thao, Phan Thi Phuong; Anh, Pham Le Nguyet; Vu, Hong Son (Vietnam Journal of Science and Technology, 2021)
Tea (Camellia sinesis) seed oil (TSO) is one of high-quality vegetable oils, similar to olive oil with high portion of unsaturated fatty acids, especially essential linoleic acid and low content of saturated fat. Solvent extraction method was used to obtain not only oil but also natural compounds from raw material. This study provides data on the physicochemical properties of TSO extracted from Trung du variety, cultivated in Phu Tho, Vietnam.